MINERALOGICAL - GEOCHEMICAL CHARACTERISTICS AND GENETIC IMPLICATION OF GUMELI (IVRINDI, BALIKESIR) TALC OCCURRENCES IN THE KARAKAYA COMPLEX (NW TURKEY) - Buyukkahraman, Gokhan; Coban, Fazli (European Scientific Journal, ESJ, 2013)
In this study, the mineralogical-geochemical characteristics and genetic implication of various talc occurrences associated with low-graded schists will be explained. Talc outcrops are located in the Karakaya complex, (Ivrindi, Balikesir). Other minerals coexisting with talcs are mainly chlorite, dolomite, magnesite, and magnetite. Geochemically, collected samples are characterized by high iron, magnesium and chrome contents. Talc occurrences have high SiO2, MgO, Fe2O3 and low Al2O3, CaO contents. Great Ni (1541 ppm), Co (82 ppm), and Cr (1711 ppm) proportions indicate that talcs were derived from a mafic or ultramafic rock (e.g. serpentinite, dunite, or harzburgite) belonging to the Karakaya complex in terms of parental affinity and should have been formed by the hydrothermal alteration of those rocks.